Analysis of the characteristics of a positive institution that assist victims of traffic accidents (Research, Society and Development, 2021)
The present study aimed to investigate an institution that develops an integrated rehabilitation program for people with physical disabilities, including victims of traffic accidents. The research was based on the Bioecological Theory of Human Development. The Ecological Insertion was used as a central methodology in a qualitative design of 45 hours of systematic visits that made possible to investigate: the dynamics of the institution, main values and beliefs of the workers practices and perceived results by professionals and users. The principles of grounded theory guided the analysis of transcriptions of the field diary observations and informal interviews that were part of the material collected in loco. The results identified three main categories consistent with characteristics of positive institutions, such as: the institutional purpose to promote empowerment and resilience, and a physical and psychological care project that emphasizes well-being and positive emotions of professionals and patients involved in the context.